Radiogenic heat production distribution of soil samples from Idi Omo, Akinyele LGA, Oyo State, Nigeria (2009)
The NaI(TI) gamma-ray spectrometer was employed to determine the concentration of naturally occurring Potassium(K-40). Uraniurn (U-238) and Thorium (Th-232) vis-à-vis the radiogenic heat production in soil samples from Idi-Omo farmland area of Akinyele, Local Government area o f Oyo state. The farmland which is at Latitude 07° 30’ 26.3" and Longitude 003° 57' 21.9" covers an area of about 80,000 square metre, and is at an average elevation of 240m above mean sea level (msl). The samples were pulverized, sealed and activities of the radiogenic isotopes in them were measured for an accumulating period of 7 hours (25200s). The elemental concentrations were determined from the gamma ray spectra. The radiogenic heat determined from activity concentrations on samples from the locality for 40k has on the average 92.86±0.02p W/Kg, while 238U has 251.26±0.61pW /Kg and 232Th has 77.210±0.03pW/Kg. The mean radiogenic heat calculated from the three radionuclides for the whole area under study is 421.3.3±0.66pW/Kg. 238U contributes 60% to the total heat production, 40K contributes 22% and 232Th contributes 18%. This makes Uranium to be the highest contributor to the total heat production in the area. However observed that the radiogenic heat production distribution in the area is low.